1997
DOI: 10.1002/ana.410410513
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral generators involved in the pathogenesis of the restless legs syndrome

Abstract: The pathophysiology of periodic limb movements and sensory leg discomfort in the restless legs syndrome is unknown. With high-resolution functional magnetic resonance imaging, we localized for the first time cerebral generators associated with sensory leg discomfort and periodic limb movements in 19 patients with restless legs syndrome. During sensory leg discomfort there was mainly bilateral activation of the cerebellum and contralateral activation of the thalamus. During the combined periodic limb movement a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
119
0
10

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 296 publications
(135 citation statements)
references
References 26 publications
5
119
0
10
Order By: Relevance
“…33 In agreement with the present study, a previous fMRI study performed on patients with RLS during combined PLMs and SLD demonstrated activation of the thalamus. 10 The thalamus is an intermediate gateway for sensory input according to cognitive requirements. 45 SPECT evaluation of RLS demonstrated increased blood flow of the thalami with increasing pain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…33 In agreement with the present study, a previous fMRI study performed on patients with RLS during combined PLMs and SLD demonstrated activation of the thalamus. 10 The thalamus is an intermediate gateway for sensory input according to cognitive requirements. 45 SPECT evaluation of RLS demonstrated increased blood flow of the thalami with increasing pain.…”
Section: Discussionmentioning
confidence: 99%
“…6 fMRI during episodes of combined sensory and motor symptoms has revealed activity in the cerebellum, red nucleus, and thalamus. 10 Patients with late-onset RLS performing regular dorsiflexion and plantar flexion of the feet in hours of daylight demonstrated greater activation of the dorsolateral prefrontal cortex of the left middle gyrus and inferior frontal gyrus and, marginally, of the cingulate gyrus. 6 Although VBM, T2 relaxometry, and fMRI have all been used in the study of patients with RLS, the 3 techniques have never been applied simultaneously in the same patient population.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…The localization of the generators of such an involuntary activity remains unknown, despite suggestions of a locus in the brainstem [3]. We report a patient with features providing important clues to the location of one of these generators.…”
Section: Introductionmentioning
confidence: 90%
“…17 Localization of the RLS induced involuntary movements and their distribution patterns favor a brainstem or spinal cord origin of movements. The ®ndings by Bucher et al 72 indicated that the red nucleus and brainstem are involved in the generation of PLM in patients with RLS. The brainstem activation may re¯ect the disinhibition eects of the reticular formation on spinal pathways.…”
Section: Possible Etiologiesmentioning
confidence: 99%